2022
DOI: 10.3390/polym14091759
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Non-Rubber Components on the Properties of Unvulcanized Natural Rubber from Different Clones

Abstract: Natural rubber from different Hevea braziliensis clones, namely RRIM600, RRIT251, PB235 and BPM24, exhibit unique properties. The influences of the various fresh natural rubber latex and cream concentrated latex on the non-rubber components related properties were studied. It was found that the fresh natural rubber latex exhibited differences in their particle size, which was attributed to the non-rubber and unique signature of clones which affect various properties. Meanwhile, the cream concentrated latex sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…To ensure a comprehensive analysis, we considered polymer melt systems composed of M polymer chains, with each chain consisting of N monomers (where M = 512 and N = 24). This choice of combination and size corresponds to a similar approach adopted in our previous work. ,, Experimental investigations have revealed that NRs with lower molecular weights exhibit enhanced mechanical and rheological properties, primarily due to a higher proportion of short chains. It is believed that the terminal groups of these short chains readily associate and interact with nonrubber components such as proteins, lipids, and sugars, thereby facilitating the formation of PJPs . Conversely, NRs with longer molecular chains exhibit inferior mechanical and physical properties as the lower density of chain end groups leads to reduced junction point formation.…”
Section: Methods and Computational Detailsmentioning
confidence: 96%
“…To ensure a comprehensive analysis, we considered polymer melt systems composed of M polymer chains, with each chain consisting of N monomers (where M = 512 and N = 24). This choice of combination and size corresponds to a similar approach adopted in our previous work. ,, Experimental investigations have revealed that NRs with lower molecular weights exhibit enhanced mechanical and rheological properties, primarily due to a higher proportion of short chains. It is believed that the terminal groups of these short chains readily associate and interact with nonrubber components such as proteins, lipids, and sugars, thereby facilitating the formation of PJPs . Conversely, NRs with longer molecular chains exhibit inferior mechanical and physical properties as the lower density of chain end groups leads to reduced junction point formation.…”
Section: Methods and Computational Detailsmentioning
confidence: 96%
“…Therefore, for each melt system, each polymer chain consists of 24 monomers. In recent experimental studies, the mechanical and rheological properties of different types of natural rubber with different molecular weight distributions have been investigated. The natural rubbers with low molecular weights have enhanced mechanical and rheological properties due to the presence of a high fraction of short chains.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…To ensure sufficient statistical sampling, we include 512 cis -1,4-PI chains in each melt system, with each chain comprising 24 monomers ( M = 512 and N = 24). This approach aligns with our previous work, where we also considered a similar combination but solely focused on the six types of α-terminals. Experimental studies have revealed that NRs with low molecular weights exhibit enhanced mechanical and rheological properties, owing to a high density of terminal groups. These terminal groups readily associate, potentially interacting with nonrubber components such as proteins, lipids, and sugars, thereby facilitating the formation of the natural network structure . In contrast, NRs with longer polymer chains exhibit poorer mechanical and physical properties due to the formation of a lower fraction of chain end group aggregates.…”
Section: Methodology and Computational Discriptionsmentioning
confidence: 54%